A Novel Approach to Proactive Primary Care–Based Case Finding and Multidisciplinary Management of Falls, Syncope, and Dizziness in a One‐Stop Service: Preliminary Results. Issue 11 (27th September 2016) - Parry, Steve W.; Hill, Harry; Lawson, Joanna; Lawson, Nick; Green, David; Trundle, Heidi; McNaught, Judith; Strassheim, Victoria; Caldwell, Alma; Mayland, Richard; Earley, Phillip; McMeekin, Peter
Abstract : National and international evidence and guidelines on falls prevention and management in community‐dwelling elderly adults recommend that falls services should be multifactorial and their interventions multicomponent. The way that individuals are identified as having had or being at risk of falls in order to take advantage of such services is far less clear. A novel multidisciplinary, multifactorial falls, syncope, and dizziness service model was designed with enhanced case ascertainment through proactive, primary care–based screening (of individual case notes of individuals aged ≥60) for individual fall risk factors. The service model identified 4, 039 individuals, of whom 2, 232 had significant gait and balance abnormalities according to senior physiotherapist assessment. Significant numbers of individuals with new diagnoses ranging from cognitive impairment to Parkinson's disease to urgent indications for a pacemaker were discovered. More than 600 individuals were found who were at high risk of osteoporosis according to World Health Association Fracture Risk Assessment Tool score, 179 with benign positional paroxysmal vertigo and 50 with atrial fibrillation. Through such screening and this approach, Comprehensive Geriatric Assessment Plus (Plus falls, syncope and dizziness expertise), unmet need was targeted on a scale far outside the numbers seen in clinical trials. Further work is needed to determine whether this approach translates into fewer falls and decreases in syncope and dizziness.